2012
DOI: 10.1055/s-0031-1299493
|View full text |Cite
|
Sign up to set email alerts
|

Subkonjunktivalanästhesie oder Vollnarkose bei der Trabekulektomie - retrospektive Analyse des perioperativen Blutungsrisikos aus Sicht des Glaukomchirurgen

Abstract: The perioperative risk profile of penetrating glaucoma surgery with subconjunctival anaesthesia seems to be similar to that of procedures under general anaesthesia. For prevention of postoperative filtering bleb bleedings, the administration of topical antiglaucomatous drugs should be stopped before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“… 53 However, this study only had a small number of cases that used subconjunctival LA, and this finding has not been replicated. Other studies have found no difference in outcome, when comparing subconjunctival LA and Ga 54 55 and subconjunctival vs Topical, 58 or subconjuctival vs retrobulbar (non-penetrating surgery). 56 A recent review article on ‘modern filtration surgery’ concluded that ‘subconjunctival anesthesia is safe’.…”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 92%
“… 53 However, this study only had a small number of cases that used subconjunctival LA, and this finding has not been replicated. Other studies have found no difference in outcome, when comparing subconjunctival LA and Ga 54 55 and subconjunctival vs Topical, 58 or subconjuctival vs retrobulbar (non-penetrating surgery). 56 A recent review article on ‘modern filtration surgery’ concluded that ‘subconjunctival anesthesia is safe’.…”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 92%
“…älter zeigt die statistische Auswertung keine Zunahme der Komplikationen mit dem Alter. Ähnlich wie in unserer früheren Studie [13] bei Patienten mit einem mittleren Alter von 65 Jahren (l " Tab. 5) zeigt sich in dieser Studie bei einem mittleren Alter von 84 Jahren auch kein erkennbar erhöhtes postoperatives Risikoprofil, unabhängig davon, ob [20].…”
Section: Diskussion !unclassified